Hubungan Tekanan Darah Dengan Kadar Ureum Dan Kreatinin Pada Pasien Diabetes Melitus Tipe 2 Di Rumah Sakit Mohammadnatsir - Ance Roslina; Amelia Eka Damayanti; Isra Thristy (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background:Diabetes mellitus is defined as a chronic metabolic disease or disorder with multi-etiology characterized by high blood sugar levels accompanied by metabolic disorders of carbohydrates, lipids, and proteins as a result of insufficiency of insulin function. Ureum and Creatinine levels are parameters for finding out kidney function and progression of chronic kidney disease as a result of Diabetes Mellitus. Methods:This research method is observational analysis with a cross sectional approach conducted at M.Natsir Hospital in Solok City in Oktober. The sampling technique is Total Sampling with a sample number of 133 respondents. Bivariate analysis was conducted to find out the correlation between blood pressure and ureum levels and creatinine patients with type 2 diabetes mellitus and tested and analyzed with spearman rho test which is useful to find out the variables with each other. Results:From the results of research found that blood pressure has a correlation with ureum and creatinine levels. Spearman Rho statistical test results obtained a value of p for blood pressure with ureum levels of 0.000 (<0.05) and a p value for blood pressure with creatinine levels of 0.000 (<0.05). Conclusion:Based on this study that there is a correlation between blood pressure and ureum and creatinine levels in patients with Type 2 Diabetes Mellitus at M.Natsir Hospital in Solok City.